Frequency of visits to a health care provider, health promoting behaviors, and perceived health status among African American women. Issue 5 (28th May 2017) - Smith, Tasia M.; Tucker, Carolyn M.; Arthur, Tya M.; Wippold, Guillermo M.; Tran, Stephanie
ABSTRACT: The primary purpose of this study was to examine whether the self-reported number of health care visits over a 1-year period was associated with engagement in health promoting behaviors (i.e., healthy eating and physical activity) and perceived health status among a cross-sectional sample of African American women who were pre-hypertensive/hypertensive and/or overweight or obese ( N = 180). The study participants were recruited in predominantly African American churches and had their data collected in April and May of 2009. Age, income, and education were also examined as moderators in the aforementioned relationships. Results revealed that the self-reported number of health care visits was significantly positively associated with healthy eating and perceived health status. Income moderated the relationship between self-reported number of health care visits and engagement in healthy eating. These results provide support for health promotion programs for African American women with program components that explain the relationships among routine care from a health care provider, engagement in health promoting behaviors, and prevention of chronic health conditions.